Estrategia de mercadeo para club ciclismo bicipeople (2024)
This undergraduate thesis addresses the various challenges faced by the Bicipeople Cycling Club, a prominent cycling community based in Barranquilla, in the aftermath of the COVID-19 pandemic. The club, which once boasted over 400 active members, experienced a significant decline in enrolment and profitability during the prolonged period of isolation. The main objective of this applied research is to design a marketing strategy for the Bicipeople club in order to improve its revenue streams and local visibility. The project is based on applied research aimed at generating practical solutions, in this case, in the business context. The project consists of two key phases: the first involved a diagnostic analysis of external and internal variables using tools such as PESTLE, Porter's Five Forces, Technological Monitoring, SWOT analysis, among others. The second phase involved the design of the strategy through a marketing plan projected for implementation in 2024. The analysis and studies conducted to design marketing strategies reveal the importance of income diversification, establishment of alliances, digital growth, sales generation through collaborations, membership increase, and digital optimization. These strategies not only counteract the club's dependence but also strengthen its connection with the cycling community. The conclusion highlights the urgent need for clarity in the marketing plan's objectives and strategic alignment with activities, which are fundamental for Bicipeople's continuous growth in both financial and digital realms. Innovation and adaptation to members' needs emerge as key elements for the club's sustained success